Improving Students' Reading Comprehension by Using Reap Strategy at the Tenth Grade of SMA Negeri 1 Gunungsitoli in 2022/2023 - Telaumbanua, Christine Eveline; Daeli, Hidayati; Maru’ao, Nursayani; Harefa, Hasrat S. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Reading comprehension is the important element that learned in English. Reading comprehension is the process of reading to get meaning and build an understanding of the text. In the reality, the students at the tenth grade of SMA Negeri 1 Gunungsitoli had a problem in reading comprehension. There were problems faced by the students: the students were not able to comprehend the text correctly. Based on the Problem, this research aimed to overcome the problem faced by the students and improved students’ reading comprehension used the REAP strategy. This research used Classroom Action Research (CAR) that consists of Planning, Action, Observation, and Reflection. The research conducted in two cycles that consist of two meetings of each cycle. The result of the research in cycle I showed there were 12 students did not pass the MCC of 21 students and the average of students’ mark was 69,44. The lowest score was 50 and the highest was 85. In the cycle II, all the students passed the MCC with the average of students’ mark was 85,55 with the lowest score was 75 and the highest score was 100. Based on the result of the research, the researcher concluded that the used of REAP strategy improved students’ reading comprehension and overcome the students’ problem in this research